Konflik Zona Ekonomi Ekslusif (ZEE) di Perairan Natuna antara Indonesia dan Republik Rakyat Tiongkok - Putri Febri Arista; Zaky Ismail (Journal Politique, 2022)
This study examines the "Exclusive Economic Zone (EEZ) Conflict in Natuna Waters Between Indonesia and China". This research was conducted based on the unresolved EEZ conflict between Indonesia and China. The purpose of this study is to find out how Indonesia manages the conflict in the Natuna waters with China, as well as to find out Indonesia's defense strategy and handling of the border area of ??the Natuna Islands and also to analyze the impact on cooperation between Indonesia and China on the conflict over this territory. The research method used in this thesis is library research where data collection uses primary and secondary data sources. The analysis uses several stages, namely topic selection, information exploration, research focus, data sources collected, reading sources, making notes, managing notes and preparing reports. The theory used is the theory of international conflict, conflict resolution. The results of this study are: first, the conflict resolution used by Indonesia is by means of litigation of International Communication. Second, the defense strategy in maintaining sovereignty used by Indonesia. Third, the impact of this regional conflict on diplomatic relations between Indonesia and China is not too significant because in the Jokowi era, it seems that Indonesia has focused on cooperation with China in various fields.